RECEPTING GENDER THOUGHTS IN MAMAOS CIANJURAN (CDA against Ceurik Rahwana and Tangis Anjani) - Barkah Barkah (LPPM of NAROTAMA UNIVERSITY, 2020)
Ceurik Rahwana and Tangis Anjani are part of Mamaos Cianjuran (a kind of opening poem), which is the oral tradition of song in West Java. Ceurik Rahwana and Tangis Anjani were chosen as study objects because of their unique gender. The study method uses critical discourse analysis. The results of the study were in the form of gender values from the local wisdom of Ceurik Rahwana and Tangis Anjani. The sympathies of this study concerning gender equality and gender balance (equilibrium), in essence, gender equality is not the same as a whole, but share the role of each other to glorify each other.